Laser re-melt technique for laser additive repair of narrow rectangular cracks in Grade 5 Titanium Alloy (Ti-6Al-4V) - Marazani, Tawanda; Madyira, Daniel. M.; Akinlab, Esther. T. (Trans Tech Publications, 2021)
Groove inaccessibility, top groove powder impedance, irregular sidewall powder delivery and lack of sidewall vertical irradiation have been reported as major limitations for the use of Laser Additive Technology (LAT) for narrow rectangular crack repair applications. As a result, most reported repair attempts were concluded unsuccessful. In the present work, a multi-track laser re-melt technique was developed for the repair of narrow rectangular cracks of sizes 2 and 3 mm, both 5 mm deep on 7 mm thick Ti-6Al-4V plates. The laser re-melt technique was carried out at controlled laser power, focal length, spot size, powder feed rate, gas flow rate and scanning speed. The repaired substrates were evaluated for defects through optical microscopy (OM) and scanning electron microscopy (SEM). The obtained results showed densely fused defect-free repaired substrates with good evolving microstructure